1984
DOI: 10.1007/bf00402008
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of a Klebsiella pneumoniae ammonium transport negative mutant (Amt?)

Abstract: The main property of an Amt- (ammonium transport negative) mutant of Klebsiella pneumoniae is its inability to accumulate NH4+ intracellularly. When growing on nitrogen sources other than NH4+, the mutant constantly looses NH3 by diffusion. This loss results in poor growth. The NH3 excretion suggests the existence of a futile cycle (NH3 loss/NH4+ reabsorption) in the wild type and possibly other bacterial strains, which do not constantly excrete NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
2
28
1
Order By: Relevance
“…The amtB gene has been implicated in the release of ammonium previously in other bacteria. Castorph and Kleiner reported that ammonium transport mutants (Amt Ϫ ) excreted ammonium in Klebsiella pneumonia (48). Meletzus et al isolated amtB mutants from A. vinelandii and showed that amtB mutants could grow on limiting ammonium but were unable to transport methylammonium (37).…”
Section: Discussionmentioning
confidence: 99%
“…The amtB gene has been implicated in the release of ammonium previously in other bacteria. Castorph and Kleiner reported that ammonium transport mutants (Amt Ϫ ) excreted ammonium in Klebsiella pneumonia (48). Meletzus et al isolated amtB mutants from A. vinelandii and showed that amtB mutants could grow on limiting ammonium but were unable to transport methylammonium (37).…”
Section: Discussionmentioning
confidence: 99%
“…Activities of glutamine synthetase, glutamate dehydrogenase and GOGAT, as well as amino acid and methylammonium transport, extracellular ammonia levels and bacterial protein contents were determined as described [14].…”
Section: Methodsmentioning
confidence: 99%
“…An AmtmUtant of Klebsiella pneumoniae which failed to grow on 1 mM NH4+ was also deficient in glutamine synthetase (4), suggesting introduction of an Ntr mutation. Servin-Gonzalez et al (26) have recently reported the isolation of methylammoniumi-resistant mutants of E. coli.…”
mentioning
confidence: 99%